A compact rectangular patch ultra wideband antenna with WLAN and ITU band rejections - Jalil Y.E.; Kasi B.; Chakrabarty C.K.; Radzi N.A.M. (Engg Journals Publications, 2023)
A simple and compact ultra-wideband (UWB) antenna integrated with dual band-notched and desirable gain characteristics is presented in this article. The proposed antenna consists of a rectangular-shaped radiator with a partial ground plane and fed by a 50 ? microstrip line. By inserting two altered H-shaped slots on the proposed radiator, dual band-notch are created to eliminate the wireless local area network (WLAN) and the International Telecommunication Union (ITU) 8-GHz band interfering signals. The presented structure gives an impedance bandwidth ranges from 2.6 to 10.8 GHz while demonstrating the band rejection performance in the targeted frequency band of 5.15 to 5.85 GHz and 8.025 to 8.4 GHz. The proposed antenna has a compact size of 23.5 21 mm2. Time domain analysis of the designed antenna indicates stable signal transmission confirming its suitability for short-range UWB impulse radios. This proposed antenna can be used to overcome the coexistence issues caused by the spectrum overlapping between wideband system and other narrowband systems.